Efficient in vitro regeneration of pathogen free mango ginger (Curcuma amada Roxb.) from rhizome bud explants - Bhattacharya, Malay; Chakraborty, Sourav (Research in Plant Biology, 2015)
Curcuma amada is an aromatic and medicinal plant belonging to Zingiberaceae. Like all other Zingiberous crops, the plant is propagated vegetatively by rhizome for which the pathogen is easily transmitted by the planting material and lack of seed set hinders breeding efforts by conventional techniques. In vitro regeneration techniques can be used to overcome this problem. Reports on production of disease free clones of Curcuma amada is lacking. So, the present study was designed. Young rhizome sprouts were cultured in Murashige and Skoog basal medium supplemented with BAP and Kinetin. BAP gave better results compared to kinetin. Combinations of cytokinins were more potential in regeneration rather than when they were used alone. Moderate rooting were observed in all the cultures. The regenerated plants showed a survival percentage of 92 % in poly cups and 98 % in field. The plantlets produced were found disease free. Â